Heat capacity measurements of the δ-phase Mg2Zr4.2Ti0.8O12 and thermodynamic modelling of the ZrO2–TiO2–MgO system. Issue 8 (July 2020) - Saenko, Ivan; Fabrichnaya, Olga
Highlights: Experimental investigation of the phase equilibria using X-ray powder diffraction. Study of thermodynamic properties of the recently discovered δ-phase in the ZrO2 –TiO2 –MgO system. Thermodynamic description of the ZrO2 –TiO2 –MgO system has been obtained for the first time. Perfect agreement between calculated and experimental data has been achieved. Abstract: Phase equilibria in the ZrO2 –TiO2 –MgO system have been studied experimentally using powder X-ray diffraction. Isothermal sections were constructed at 1475 and 1555 K. The eutectoid reaction of δ-phase ↔ Mg2 TiO4 +T-ZrO2 +MgO and the solid transition reaction of δ-phase + MgTiO3 ↔ Mg2 TiO4 + T-ZrO2 were determined at temperatures 1503 and 1535 K, respectively. Heat capacity measurements for the δ-phase have been obtained in the temperature range from 210 to 1370 K. Debye temperature of the δ-phase was estimated. Standard entropy for the δ-phase was evaluated. Based on the obtained experimental data, a self-consistent thermodynamic description of the ZrO2 –TiO2 –MgO system has been developed.